Re-investigating Consumption-related Emotions Scales: Some Initial Findings - Butcher, Luke; Phau, Ian; Marchegiani, Chris (Australian and New Zealand Marketing Academy, 2012)
This study adapts and tests items from prominent and widely adopted consumer-related emotions measures and proposes a set of items which capture emotions towards a product shown in an advertisement prior to consumption, whilst addressing some of the methodological concerns of these previous measures. The final scale contains 23 emotion items loading on four factors; Positive, Negative, Skepticism, and Un-stimulated. This provides a contrasting perspective to the hierarchical approach to consumer-related emotions adopted by many scholars.